MUET as a predictor of academic achievement in ESL teacher education - Othman, Juliana; Nordin, A.B. (Universiti Kebangsaan Malaysia Press, 2013)
One of the indicators of English language proficiency used by Malaysian public universities is the Malaysian University English Test (MUET). This study seeks to examine whether MUET is an accurate predictor of academic performance of a group of English teacher education students. The participants for this study consisted of 111 first and second year students who were enrolled in a B. Ed Teaching English as a Second Language (TESL) program at a local public university. A general linear multivariate regression was conducted using the SPSS for the overall score of the MUET together with their scores on each of the test components and the students CGPA (Cumulative Grade Point Average). The analysis was carried out to identify important predictors of academic achievement by correlating each of the independent predictor variables with each other as well as with the academic achievement criterion. The results of the multiple regression analysis revealed that reading and listening components were significant predictors of students’ academic achievement. These findings seem to indicate that the different components of the MUET can be used to predict students’ academic performance more accurately than the overall MUET score itself. However, there is a need for continuing predictive validity studies in different contexts. Context specific studies are important as they provide empirical evidence and contribute to an increasing literature on the relevance of MUET in higher education settings.